The The Effect of Anastatica hierochuntica (Fatimah Grass) on Oxytocin Levels and Uterine Contractions: an Experimental Study - Siswina, Tessa; Akbarini, Oon Fatonah; Fajrin, Dessy Hidayati (Women, Midwives and Midwifery, 2025)
Background: One of the global targets of the Sustainable Development Goals (SDGs) in 2030 is to reduce maternal mortality rate (MMR) to below 70/100.000 live births and infant mortality rate (IMR) to 2/1000 live births. One of the factors that complicates childbirth is inadequate contractions, which is influenced by oxytocin. Oxytocin is a hormone secreted by neurohypophysis that causes uterine contractions during delivery. One of the traditional herbs that can be used to increase contractions is Fatimah grass (Anastatica hierochuntica). A. hierochuntica was used in Arabs, Indonesia, and Malaysia (63,9%) to shorten labor time, breastfeeding, and reduce postpartum hemorrhage by traditional. Purpose: This purpose was to identify the potency of A. hierochuntica as an oxytocin stimulator by invitro and invivo study. Methods: The method used a true experiment with a double-blind randomized controlled trial (RCT) and posttest design with a control group design of four groups (G1-G4). The research subject was 28 pregnant mice. Results: The results of this research were A. hierochuntica has flavonoids, terpenoids, steroids, alkaloids, phenolic, tannin, and saponin secondary metabolites. A. hireochuntica have activity to increase the oxytocin hormone levels in pregnant mice (G1 averaged 49.79; G2 averaged 83.38; G3 averaged 91.05; and G4 averaged 101.39 pg/ml), increase the contraction of onset time (G2 averaged 17; G2 averaged 14.71; and G4 averaged 13.57 minutes) and shorten labor time. Conclusion: The use of A. hierochuntica decoction significantly increases levels of the oxytocin and uterine contractions. The use of A. hireochuntica in delivery women as traditional herbs requires monitoring from health workers because of its strong ability to increase contractions, and must be done carefully with health worker recommendation.